Reversibility Test of Oil Demand Function of OECD Countries Importing Oil from Iran with an Emphasis on Technological and Environmental Considerations: Symmetric and Asymmetric Models - Bahmanshir, Reza Darisavi; Meidani, Ali Akbar Naji; Mashhadi, Mahdi Khodaparast; Salehnia, Narges (International Journal of Energy Economics and Policy, 2018)
The study aimed to estimate the oil demand function of the OECD countries importing oil from Iran based on symmetric and asymmetric specification. To estimate symmetric and asymmetric patterns in this study, data from 1970 to 2014 for OECD countries importing oil from Iran including France, Germany, Greece, Italy, Japan, Poland, Spain, Turkey, England, South Korea, Czech, Netherlands and Belgium were used. The results of the panel root test showed the first-order difference reliability of the variables and the co-integration test confirmed a long-term relationship between the variables. Therefore, the models were estimated using the fully modified ordinary least square method (FMOLS). The results of the model estimation indicated the irreversibility of the oil demand function of the OECD countries importing oil from Iran. Keywords: Oil demand function reversibility, OECD countries, modified ordinary least square method, panel co-integration test JEL Classifications: D43, E31, L71